(untitled) (Research, Society and Development, 2022)
Dental traumas are frequent episodes caused by several factors that can result in injuries to dentoalveolar tissues. The severity of the injury can cause irreversible damage to the affected structures, which can lead to loss of the dental element. To report the clinical case of a patient who suffered dental trauma to the maxillary central incisors resulting in a complicated crown-radicular fracture. Patient M.G.S.M.A., female, 09 years old, attended the UniFTC Dental School Clinic accompanied by her mother complaining of “My daughter fell off her bicycle and broke her tooth”. Upon clinical intra-oral examination and analysis of imaging tests, it was observed that the patient had a cororadicular fracture complicated by the fact that it was a tooth with incomplete root formation and a crack in the root of the unit was diagnosed, a conservative endodontic treatment was performed, using the technique of apexification and total filling of the canal with Mineral Trioxide Aggregate. The treatment of this case required a multidisciplinary approach, where other dental specialties integrated their knowledge to solve the case. After 06 months, the dental unit was reassessed, and absence of painful symptoms and apical bone repair was observed. At the end of the clinical case, we can observe that the treatment of traumatized teeth is a challenge for Endodontics and this must be carried out in an integrated way with other dental specialties in order to restore the functional and aesthetic characteristics of the teeth, resulting in positive psychosocial changes in the personal life of the patient. patient.